A new paradigm for tumor immune escape: β-catenin-driven immune exclusion. Issue 1 (15th September 2015) - Spranger, Stefani; Gajewski, Thomas F.
Abstract : Increasing evidence is emerging that immunotherapeutic interventions, including checkpoint blockade, are predominantly effective in patients with a pre-existing T cell-inflamed tumor microenvironment. Understanding the mechanisms leading to a non-T cell-inflamed microenvironment are crucial for the development of novel treatment modalities to expand the fraction of patients benefiting from immunotherapy. Based on the hypothesis that one source of inter-patient heterogeneity would lie at differential activation of specific oncogene pathways within the tumor cells themselves, our group recently observed that tumor-cell intrinsic activation of the WNT/β-catenin pathway correlates with absence of T cells from the microenvironment in metastatic melanoma. Genetically-engineered mouse models confirmed a causal relationship, via a mechanism of failed Batf3-lineage dendritic cell recruitment. Hence, tumor cell-intrinsic activation of β-catenin is the first oncogenic pathway demonstrated to exclude the anti-tumor immune response, revealing a potential therapeutic target for improving immunotherapy responsiveness.